Design of Bluetooth Integrated Circular Patch Ultra Wide Band with Ground Slot for WLan Applications - Dennis Cahaya Satriawan; Busono Soerowirdjo (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2020)
A microstrip feedline dual band circular monopole antenna operating over Bluetooth (2.4 – 2.48 GHz) and Ultra wideband (UWB: 3.1-10.6GHz) frequency bands is designed and investigated for wireless applications. The UWB frequency is achieved by modifying the patch radiating monopole by adding slots and destructive ground plane. Further, with the addition of a slot in the radiation patch that is placed in the central portion of the radiating patch and then etching a half wavelength circular arc from the radiating patch a dual band frequency operation archive over Bluetooth and UWB band. The proposed antenna is simulated using electromagnetic simulation software Ansoft HFSS Ver 15.0. The proposed antenna is realized on FR-4 dielectric substrate having a dielectric constant of 4.4 and loss tangent of .02. The antenna covers the dual bands of operation i.e. Bluetooth (2.4-2.48GHz) bandwidth obtained 182.3 MHz and UWB (3.1-10.6 GHz) bandwidth obtained 8.999 GHz with reflection coefficient -10dB and value of VSWR 2. The antenna also exhibits stable radiation patterns for the entire UWB and aforementioned integrated lower frequency bands